Comparison of Oxoferrin (Tetrachlorodecoxide) Drops Dressing versus Normal Saline Dressings in Management of Diabetic Foot Ulcers - Khan, Muhammad Zargham Nasir; Abbasi, Shehzad Ahmed; Tasneem, Nauman; Tahir, Muhammad Nafe Bin; Mashhadi, Syeda Rida; Abdullah, Sidra (Pakistan Armed Forces Medical Journal, 2025)
Objective: To compare the wound outcome of “Oxoferrin (Tetrachlorodecoxide) drops dressing” versus “normal saline dressings” in management of diabetic foot ulcers.Study Design: Quasi-experimental study.Place and Duration of Study: Pakistan Air Force Hospital Mushaf, Sargodha Pakistan, from May 2023 to Feb 2024.Methodology: We included 210 patients with diabetic foot ulcers. 10 patients were excluded making final sample of 200 which were divided into “Oxoferrin (Tetrachlorodecoxide) drops dressing” & “normal saline dressings” Groups. Patients were treated for four weeks and were then assessed for outcomes.Results: No difference was observed between Groups for baseline size of wound (p=0.809). “Size of wound” after four weeks of therapy in “Oxoferrin (Tetrachlorodecoxide) drops dressing” Group (A) was 131.70±11.83 cm2 while in “normal saline dressings” Group (B) it was 151.74±13.22 cm2, (p